Molecular cloning and characterisation of a novel putative MYB-related transcription factor (ClMYB1R1) from Curcuma longa L. - Aparna, R.S.; Mol, P. Prashina; Sheeja, T.E. (Journal of Plantation Crops, 2021)
Turmeric (Curcuma longa L.) is gaining immense global importance due to the presence of curcumin that contributes to its immunomodulatory properties. Curcumin, a phenylpropanoid derivative, is the most important secondary metabolite present in turmeric rhizomes and understanding the regulatory mechanism of curcumin biosynthesis is hence important. In plants, activator and repressor type transcription factors (TFs) of the myeloblastosis (MYB) family have been found to regulate the biosynthesis of secondary metabolites. MYB TF genes of the R2R3 class were identified by RNA-Seq based approach from turmeric. The present study involves RNA seq based identification, cloning and characterisation of a novel MYB TF of the 1R class. Gene-specific primers were used to amplify 1R MYB from the rhizome, and it was sequenced to give a full-length gene of 1056 bp. The identified MYB gene was designated as ClMYB1R1 and consisted of a 693 bp open reading frame (ORF) which encodes a 230 amino acid length protein with a molecular mass of 25 kDa and pI 9.51. The protein was predicted to consist of a single helix-turn-helix MYB-like motif and other highly conserved residues. ClMYB1R1 expression varied in different genotypes and tissues. UV-C light was found to upregulate, while NaCl and nutrient stresses down-regulated the expression. The expression showed a positive correlation with a candidate pathway gene ClPKS11 under all of the above experimental conditions, indicating the putative role of ClMYB1R1 in regulating curcumin biosynthesis.